2020
DOI: 10.3390/polym12010199
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonic Acid Coupling Agent Modification of HAP Nanoparticles: Interfacial Effects in PLLA/HAP Bone Scaffold

Abstract: In order to improve the interfacial bonding between hydroxyapatite (HAP) and poly-l-lactic acid (PLLA), 2-Carboxyethylphosphonic acid (CEPA), a phosphonic acid coupling agent, was introduced to modify HAP nanoparticles. After this. the PLLA scaffold containing CEPA-modified HAP (C-HAP) was fabricated by selective laser sintering (frittage). The specific mechanism of interfacial bonding was that the PO32− of CEPA formed an electrovalent bond with the Ca2+ of HAP on one hand, and on the other hand, the –COOH of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Moreover, the scaffolds' architecture seems to provide good conditions for cells' growth and do not hamper their natural behaviors [38]. The findings show that all of the prepared scaffolds can be considered to be non-toxic and can be used for further studies, which should be focused on in vivo experiments [42][43][44][45][46].…”
Section: Cytotoxicity Study Of the Prepared Scaffoldsmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the scaffolds' architecture seems to provide good conditions for cells' growth and do not hamper their natural behaviors [38]. The findings show that all of the prepared scaffolds can be considered to be non-toxic and can be used for further studies, which should be focused on in vivo experiments [42][43][44][45][46].…”
Section: Cytotoxicity Study Of the Prepared Scaffoldsmentioning
confidence: 90%
“…Their incorporation should provide extraordinary properties to the hierarchized scaffolds and promote biomineralization process [27,[32][33][34][35]. The proposed structure should enable cell adhesion and proliferation, along with osteogenic differentiation, since they meet architectural requirements for bone-tissue regeneration [40,[42][43][44][45][46].…”
Section: Morphology Study Of the 3d Scaffolds And Its Componentsmentioning
confidence: 99%
“…Recent advances have demonstrated that inducing the bone formation to restore the normal bone homeostasis is efficient for osteoporosis treatment 1 . Although osteogenesis induced by biological materials has gained much attention, classic methods are still applied in the studies of osteogenic differentiation of MSCs 2‐5 . Human umbilical cord‐derived mesenchymal stem cells (hUC‐MSCs), a stem cell population, possess many advantages relative to other cell sources, 6 including easily isolated, abundantly supply, 7 low immune rejection, 8 self‐renewing ability and multipotency 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Girish et al [19,20] have studied the graphite particles reinforced Zn matrix composites and found that the hardness and strength were enhanced. However, they found it was difficult to form good interfacial bonding in metal matrix composite due to the large physical and chemical differences between the matrix and the reinforcing phase [21][22][23][24]. This will reduce the load transfer capacity of the enhancement phase [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%